AN ANALYSIS OF POLITENESS STRATEGIES USED BY EFL STUDENTS IN MAKING REQUEST - Indah Triana Juliari, I Gusti Ayu; Yuniari, Ni Made (Widya Accarya, 2019)
Abstract This study investigates politeness strategies used by EFL students in teaching and learning process. It focuses on the types of politeness strategies namely positive and negative politeness strategy that occurs in making request. This study used descriptive qualitative method in which describe the phenomenon when the students had speaking course in the classroom. The subject of this study were the second semester of English Education Department students who followed the speaking class. This research used purposive sampling in choosing the sample. There were 12 samples chosen randomly from the population. Five of them were male and seven of them were female. The data were collected by some instruments, namely: observation sheet, video recorder and field note. After collecting the data, the researcher transcript and analyze the data by using politeness theory. The result of this study showed that, there were 12 positive politeness and 14 negative politeness strategies used by EFL students in teaching and learning process especially in making request. There were 3 types of positive politeness strategies used by EFL students, namely: be optimistic, presuppose/raise/assert common ground, offer and promise. Meanwhile, there were also 3 types of negative politeness strategies occurs, namely: Impersonalized S and H, Be conventionally indirect, and Question, hedge. From the finding, negative politeness strategy that mostly used by EFL students in teaching and learning process especially in making request. Keywords: Positive politeness strategies, negative politeness strategies, EFL students, teaching and learning process